Resource partitioning in three congeneric sympatrically breeding seabirds: Foraging areas and prey utilization. (1st July 2014) - Robertson, G. S.; Bolton, M.; Grecian, W. J.; Wilson, L. J.; Davies, W.; Monaghan, P.
Abstract: Morphologically similar sympatric species reduce competition by partitioning resources, for example by occupying different dietary niches or foraging in different areas. In this study, we examine the foraging behavior of Arctic ( Sterna paradisaea ), Common ( Sterna hirundo ), and Roseate terns ( Sterna dougallii ) breeding on Coquet Island, northeast England, using colony-based observations and coincident at-sea visual tracking of foraging birds to quantify interspecific overlap in prey selection and foraging areas. Although visual tracking methods have been used in previous studies, our study is the first example of this method being used to quantify multi-species overlap in foraging areas and the first time Roseate Tern foraging locations have been conclusively identified using a visual tracking method. Percentage overlap in foraging areas varied among species with Arctic and Common terns sharing a higher percentage of their foraging range with each other (63%) than either species did with Roseate Terns (Common = 41% and Arctic = 0%). Arctic and Common terns utilized similar foraging areas and partitioned resources by diet while Roseate Terns differed from other species in both diet and foraging area. Arctic and Common terns varied provisioning rate, prey length, and foraging areas with increasing brood age, while Roseate Terns fed similar prey and foraged consistently inshore. Although there were some similarities in areas utilized by these species, there were sufficient differences in behavior to minimize interspecific competition. Our study further demonstrates the successful use of a visual tracking method to show how morphologically similar sympatric seabird species partition resources by diet, foraging area, and response to increasing brood age.